Inhibitor development and clinical characteristics in children with severe hemophilia A in the ATHN 8 US cohort study - Courtney D. Thornburg; H. Marijke van den Berg; Martin Chandler; Lynn Malec; Matthew Manuel; Carrie O’Neill; Michael Recht; Elizabeth Taggart; Shannon L. Carpenter; Christine Knoll; Lynn Malec; Michael Wang; et al. (Blood Vessels, Thrombosis & Hemostasis, 2025)
Abstract: Clotting factor concentrate (CFC), used to treat and prevent bleeding in hemophilia, is rendered ineffective if clotting factor neutralizing antibodies (inhibitors) develop. Inhibitors occur most often in children, early in treatment. The American Thrombosis and Hemostasis Network (ATHN) 8: US Cohort Study of Previously Untreated Patients (PUPs) with Congenital Hemophilia, conducted in children born in 2010 to 2020 with severe or moderate hemophilia, was designed to determine the percentage of participants who developed a confirmed, clinically significant inhibitor within the first 50 CFC exposure days (EDs). Cox proportional hazards models were used to evaluate risk factors for inhibitor development in PUPs with severe hemophilia A (HA). A total of 171 males with severe HA enrolled: 39 (22.8%) developed an inhibitor, 30 (17.5%) developed a high-titer inhibitor, and 9 (5.3%) developed a low-titer inhibitor; 82.1% within 20 EDs. Product exposure at <1 month (hazard ratio [HR], 2.57; 95% confidence interval [CI], 1.22-5.44), large structural changes (HR,16.59; 95% CI, 1.94-142.20), and nonsense variants (HR, 12.53; 95% CI, 1.41-111.49) were associated with inhibitor development. Overall, inhibitor development remains a significant CFC complication especially in the first 10 to 20 EDs. Further study should evaluate the impact of new treatments on inhibitor rates and age at inhibitor development and identify strategies to reduce inhibitor development.